2006
DOI: 10.1159/000091720
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Synapsin III –196 Promoter Mutation in Schizophrenia and Bipolar Disorder

Abstract: Background: The 22q13-linked gene synapsin III is a positional candidate gene for schizophrenia (SZ). One interesting synapsin III single nucleotide polymorphism (SNP), –196G/A, has been identified in the promoter region. The –196A allele results in a 6/8 base match to the core recognition octamer sequence for Oct-1, a member of the POU family of transcription factors. Objective: To determine whether or not the –196 SNP is associated with either SZ or bipolar disorder (BD). Methods: A case control comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…A growing body of evidence suggests that disorders like schizophrenia, bipolar disorder and ASD which show genetic overlap [97] involve synaptic abnormalities that predispose individuals to these conditions. Mutations affecting a number of synaptic proteins have been observed in schizophrenia, bipolar disorder and ASD [98][103]. GluD1 is developmentally expressed and has been shown to affect presynaptic differentiation and synapse formation in in vitro systems [8].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that disorders like schizophrenia, bipolar disorder and ASD which show genetic overlap [97] involve synaptic abnormalities that predispose individuals to these conditions. Mutations affecting a number of synaptic proteins have been observed in schizophrenia, bipolar disorder and ASD [98][103]. GluD1 is developmentally expressed and has been shown to affect presynaptic differentiation and synapse formation in in vitro systems [8].…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs133945 is potentially functional, because an ATTT motif is located at position -196 that resembles the octamer sequence recognized by members of the POU family of transcription factors [123]. Indeed, the G-allele of this SNP has consistently resulted in greater binding to brain proteins than the A-allele, suggesting that this polymorphism has an effect on DNA-protein complexes [123]. The functional relevance of rs133946 has not been investigated.…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
“…Interestingly, no striking differences in the frequencies of these SNPs were observed in schizophrenia [113, 123] or bipolar disorder [123], although there were trends towards significance in some ethnic samples, suggesting that the studies were underpowered. However, there were significant differences in protein-DNA interactions using protein extracts from postmortem brains of individuals with bipolar disorder and synthetic DNA corresponding to alleles of rs133945 [123].…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several association studies of SYN3 and schizophrenia in different populations, including those of Asian, European and African ancestry, but most of the results are negative, and positive findings are not consistent across studies [8;12;13;1720;22]. For example, Porton and colleagues found that a rare, missense polymorphism, S470N, appeared more frequently in European individuals with schizophrenia (5%) than in controls (0.9%) (p=0.0048)[19].…”
Section: Introductionmentioning
confidence: 99%